A Conceptual Model for Responsible AI Integration in Public-Facing Digital Services and Platform Governance - Bolanle A. Adewusi,; Bolaji Iyanu Adekunle,; Sikirat Damilola Mustapha,; Abel Chukwuemeke Uzoka, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
As artificial intelligence (AI) increasingly powers public-facing digital services, ensuring its integration is guided by ethical, transparent, and accountable frameworks has become critical. This study proposes a conceptual model for responsible AI integration in the design, delivery, and governance of digital platforms within the public sector. The model is informed by a systematic synthesis of academic literature, government reports, and real-world case studies spanning healthcare, digital identity systems, e-governance platforms, and intelligent public services from 2015 to 2024. The review highlights that while AI offers transformative benefits such as automation, personalization, and predictive analytics it also introduces risks including algorithmic bias, opacity, surveillance concerns, and inequitable access. The proposed model comprises five interlocking components: stakeholder-centered design, algorithmic transparency, regulatory compliance, human oversight, and adaptive feedback loops. These components are aligned with international principles such as fairness, explainability, accountability, and human-centric innovation. At the heart of the model is the integration of Responsible AI practices into platform governance mechanisms, ensuring that public trust, user agency, and digital equity are preserved. The model advocates for inclusive stakeholder engagement at every stage from needs assessment to deployment and monitoring alongside policy instruments that support continuous evaluation and redress mechanisms. Furthermore, it emphasizes cross-sector collaboration between technologists, policymakers, ethicists, and civil society organizations to ensure multidimensional accountability. Case insights from AI-powered welfare systems, smart city initiatives, and intelligent public health platforms demonstrate both the potential and pitfalls of AI when ethical considerations are not systematically embedded. The model offers a flexible blueprint adaptable to various scales of governance and institutional capacities, providing a pathway to bridge technological advancement with democratic values. This conceptual model contributes to the growing discourse on digital trust and responsible innovation, serving as a strategic tool for governments, platform designers, and regulators seeking to deploy AI technologies in ways that enhance service delivery while safeguarding public interest.
Keywords: Responsible AI; Public Sector Innovation; Platform Governance; Ethical AI; Digital Services; Algorithmic Accountability; Human Oversight; Transparency; AI Regulation; Conceptual Model